1998
DOI: 10.1093/ajcp/109.5.533
|View full text |Cite
|
Sign up to set email alerts
|

Serum Percent–Free PSA Does Not Predict Extraprostatic Spread of Prostate Cancer

Abstract: Percent-free prostate-specific antigen (proportion of free prostate-specific antigen [PSA] to total PSA) has been shown recently in studies on frozen serum samples to be more useful than total PSA alone in distinguishing prostate cancer from benign conditions of the prostate gland. The primary purpose of our study was to determine whether percent-free PSA could predict extraprostatic spread of prostate cancer. We also sought to evaluate the freeze-thaw stability of free PSA. Percent-free PSA values in fresh se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
2
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 15 publications
2
21
2
1
Order By: Relevance
“…In a study of 288 patients with clinically localized prostate cancer who underwent radical prostatectomy, 97.2% had less than 25% free PSA and no relation was found between this parameter and the pathological stage (Partin et al, 1996). In another study carried out on 70 patients, the conclusion was that the percentage of free PSA did not predict whether adenocarcinoma had spread beyond the prostate gland (Henricks et al, 1996). In the present series of 118 patients with prostate cancer, we found that the percentage of free PSA was not related to clinical stage, although the group of patients with metastatic disease showed a significantly lower ratio, p , 0.04.…”
Section: Discussioncontrasting
confidence: 64%
“…In a study of 288 patients with clinically localized prostate cancer who underwent radical prostatectomy, 97.2% had less than 25% free PSA and no relation was found between this parameter and the pathological stage (Partin et al, 1996). In another study carried out on 70 patients, the conclusion was that the percentage of free PSA did not predict whether adenocarcinoma had spread beyond the prostate gland (Henricks et al, 1996). In the present series of 118 patients with prostate cancer, we found that the percentage of free PSA was not related to clinical stage, although the group of patients with metastatic disease showed a significantly lower ratio, p , 0.04.…”
Section: Discussioncontrasting
confidence: 64%
“…M, molecular mass standards with shown masses in kilodaltons. (37)(38)(39). By using a polyclonal antibody against hK3, we performed Western blots of seminal plasma, prostate extracts and at different time points of the activation of pro-hK3 by hK5.…”
Section: Resultsmentioning
confidence: 99%
“…Their study population consisted of men undergoing radical prostatectomy for prostate cancer, 44% of w h o m d e m o n s t r a t e d extraprostatic spread of the tumor. Total PSA values were significantly different b e t w e e n the organconfined and extraprostatic groups, but there was no significant difference in percent-free PSA (see Fig 1 and 2 in Henricks et al article 1 ). Inspection of these figures reveals a large overlap of values between the two groups; there is no decision level that would provide a reasonable sensitivity and specificity for either total PSA or percent-free PSA (see Fig 5 in Henricks et al article 1 ).…”
Section: American Journal Of Clinical Pathologymentioning
confidence: 81%
“…Total PSA values were significantly different b e t w e e n the organconfined and extraprostatic groups, but there was no significant difference in percent-free PSA (see Fig 1 and 2 in Henricks et al article 1 ). Inspection of these figures reveals a large overlap of values between the two groups; there is no decision level that would provide a reasonable sensitivity and specificity for either total PSA or percent-free PSA (see Fig 5 in Henricks et al article 1 ). Percent-free PSA also failed to predict the pathologic stage of the tumors and was only weakly correlated to the Gleason score.…”
Section: American Journal Of Clinical Pathologymentioning
confidence: 81%
See 1 more Smart Citation